Conceptualizing Emotions Along the Dimensions of Valence, Arousal, and Communicative Frequency – Implications for Social-Cognitive Tests and Training Tools - Hepach, Robert; Kliemann, Dorit; Grüneisen, Sebastian; Heekeren, Hauke R.; Dziobek, Isabel (Frontiers in Psychology, 2011)
Background and Objectives. Emotion words are mostly characterized along the classic dimensions of arousal and valence. In the current study we sought to complement this characterization by investigating the frequency of emotions in human everyday communication, which may be crucial information for designing new diagnostic or intervention tools to test and improve emotion recognition.Methods. One hundred healthy German individuals were asked to indicate the valence and arousal of 62 emotion words in a questionnaire. Importantly, participants were additionally asked to indicate the frequency with which they experience each emotion themselves and observe it in others. Results. Positive emotions were judged to occur more often than negative emotions in everyday life. The more negatively valenced emotions were rated to be observed more often in others than experienced in one-self. On the other hand more positively valenced emotions were experienced more often in one-self than they were observed in others. Finally, increasing age was associated with a decrease in the frequency of observing an emotion in other people. Limitations. Future studies with larger sample sizes are needed to ascertain if the findings also apply to other cultural and language contexts. Conclusions. These results imply a greater frequency of positive emotions than negative emotions in everyday communication. The finding of such a bias towards positive emotions can guide the selection of emotion words for implementation in socio-emotional intervention tools. Such a selection may represent an effective means for improving social cognitive functioning in people with socio-cognitive impairments.